FACTORS THAT INFLUENCE ATTITUDE AND INTENTION TO BUY IN HALAL-LABELED SANDALS - Ikhwan A., Raffi
Most studies on Halal products have concentrated on food and cosmetics. The purpose of this study is to investigate the factors that influence the attitude and purchasing intention of non- food Halal products in the context of sandals. This research is based on the principle of reasoned action. As antecedents of attitude, it comprises knowledge, religiosity, and perceived usefulness of the Halal designation. A self-administered online questionnaire was used in this study. A non-probability sampling technique was used to obtain data from an online survey (convenience sampling). The study received 260 valid replies in total. Muslim customers aged 39-45 made up the majority of the respondents (28,1%), followed by those >46 years old (26.5%). Partial least square structural equation modeling was used to examine the data. The results show that the knowledge of Halal does not have a positive effect on attitudes. Subjective norms, religiosity, have influence attitudes toward Halal labeled sandals as well as perceived usefulness. As a result, attitude toward Halal-labeled detergent influences intention to purchase Halal-labeled sandals. This study also reveals that perceived usefulness of the Halal label influence the intention to use Halal sandals. In some countries, such as Indonesia, Halal labeling on all products has recently become mandatory by legislation. This study examines the causes and implications of a non-food Halal product category other than cosmetics. It also provides insights into Muslim consumers' perceptions about Halal labeled products.